Eficácia de milho transgênico tratado com inseticida no controle da lagarta-do-cartucho no milho safrinha no estado de São Paulo, Brasil - Michelotto, Marcos Doniseti; Neto, Jacob Crosariol [UNESP]; Pirotta, Melina Zacarelli [UNESP]; Duarte, Aildson Pereira; de Feitas, Rogério Soares; Finoto, Everton Luis (FapUNIFESP (SciELO), 2017)
Several genetically modified maize events expressing insecticidal proteins from Bacillus thuringiensis (Bt) have been commercially available in Brazil, intended to control of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae). The objective of this study was to evaluate the efficiency of transgenic (Bt) and conventional (non-Bt) hybrids in the control of fall armyworm, treated or not with insecticides throughout three late growing seasons. To this end, trials were conducted at three locations in the state of São Paulo, in a randomized complete block design, in factorial arrangements with 5x4, 5x4 and 8x4 factors, respectively. The first factor consisted of the number of commercial hybrids of different companies. The second factor was represented by the different control managements of insect (non-Bt hybrid with and without insecticide; Bt hybrid with and without insecticide). The damage caused by fall armyworm was evaluated on a visual 1-9 scale, from score 0 (no damage) to 9 (totally destroyed whorl), and grain yield (kg ha-1). The data were analyzed by analysis of variance and the means compared by the Tukey test at 5% probability for each parameter evaluated at each location. For the Bt hybrids, the damage scores attributed to fall armyworm were lower and the proteins Cry 1F, Cry 1A105 and VIP3Aa20 were the most efficient in reducing leaf damage. Insecticide applications proved efficient in reducing leaf damage caused by the pest. Application of insecticides to Bt hybrids generally reduced leaf damage, especially for Cry1Ab-producing hybrids, which were the least effective in reducing pest damage without insecticides.
Efficacy of transgenic mayze insecticide treatment to control fall armyworm in late-season maize in São Paulo state, Brazil
Keywords: Pest management; Spodoptera frugiperda; Zea mays